SAT0352 Analysis of Varicella-Zoster Virus in Temporal Artery Biopsies Positive and Negative for Giant Cell Arteritis. (15th July 2016) - Muratore, F.; Croci, S.; Tamagnini, I.; Zerbini, A.; Belloni, L.; Bellafiore, S.; Boiardi, L.; Bisagni, A.; Parmeggiani, M.; Cavazza, A.; Salvarani, C.
Abstract : Background: Recent studies found an high prevalence of varicella-zoster virus (VZV) infection in temporal arteries (TAs) from both temporal artery biopsy (TAB)-positive and TAB-negative giant cell arteritis (GCA) patients compared to controls, suggesting that VZV infection may trigger the inflammatory cascade that characterizes GCA (1, 2). Objectives: To analyze VZV infection in TAs from patients with TAB-positive GCA (biopsy-proven GCA), TAB-negative GCA (patients with negative TAB and a final diagnosis of GCA) and controls (patients with negative TAB and a final diagnosis different from GCA). Methods: A total of 75 formalin-fixed, paraffin-embedded (FFPE) TABs performed between 2009 and 2012 at a single institution from 30 TAB-positive GCA patients, 15 TAB-negative GCA patients and 30 controls were retrieved. Six 5-μm sections of all FFPE TABs were cut. The first section was analyzed by immunohistochemistry using mouse monoclonal anti-VZVgE IgG1 antibody (Santa Cruz Biotechnology) and OptiView DAB Detection Kit (Ventana, Roche). DNA was extracted from the remaining 5 sections with the QIAamp DNA FFPE tissue kit (Qiagen) and analyzed by real-time polymerase chain reaction for the presence of VZV DNA (VZV ELITe MGB kit, ELITechGroup). In addition DNA was extracted with the RNA/DNA/Protein purification kit (Norgen Biotek) from 5 positive TABs of 2 mm length obtained from GCA patients and immediately stored frozen at -80°C. Beta globin (included in the VZV ELITe MGB kit) and a short intergenic region were amplified to verify the quality of DNA. Results: 60/75 (80%) patients were female. Mean (± SD) age at TAB was 72.1 (± 8.3) years. There were no significant differences in sex and age distributions between TAB-positive GCA, TAB-negative GCA and controls. Median (Q1, Q3) time from symptoms onset to TAB was 11 (5.5, 19.3) weeks for TAB-positive GCA, 15 (9, 20) weeks for TAB-negative GCA and 12 (6, 41.6) weeks for controls, p=0.414. 22/30 (73.3%) TAB-positive GCA, 8/15 (53.3%) TAB-negative GCA and 20/30 (66.7%) controls were receiving prednisone at the time TAB was performed, p=0.407. Immunohistochemical analysis detected VZV antigen in 1/30 TAB-positive GCA, 0/15 TAB-negative GCA and 0/30 controls, p=0.467. DNA obtained from all TABs was amplifiable. DNA obtained from frozen TABs was more concentrated than that obtained from FFPE TABs which allowed to load a higher quantity of DNA per reaction increasing assay sensitivity.VZV DNA was not found in any of the FFPE TABs as well as in frozen TABs but was clearly detected in FFPE skin lesions from patients with active infection (threshold cycle for VZV DNA =26 when 0.5 ng of DNA were amplified). Conclusions: Our data do not support a role for VZV infections in the etiopathogenesis of GCA. References: Gilden D, et al. Prevalence and distribution of VZV in temporal arteries of patients with giant cell arteritis. Neurology. 2015 May 12;84(19):1948–55. Nagel MA, et al. Analysis of Varicella-Zoster Virus in Temporal Arteries Biopsy Positive and Negative for Giant Cell Arteritis. JAMA Neurol. 2015 Nov 1;72(11):1281–7. Disclosure of Interest: None declared